Dipeptidyl peptidase-IV inhibits glioma cell growth independent of its enzymatic activity - Busek, Petr; Stremenova, Jarmila; Sromova, Lucie; Hilser, Marek; Balaziova, Eva; Kosek, Dalibor; Trylcova, Jana; Strnad, Hynek; Krepela, Evzen; Sedo, Aleksi (The international journal of biochemistry & cell biology, 2012)
Malignant gliomas exhibit abnormal expression of proteolytic enzymes that may participate in the uncontrolled cell proliferation and aberrant interactions with the brain extracellular matrix. The multifunctional membrane bound serine aminopeptidase dipeptidyl peptidase (DPP)-IV has been linked to the development and progression of several malignancies, possibly both through the enzymatic and nonenzymatic mechanisms. In this report we demonstrate the expression of DPP-IV and homologous proteases fibroblast activation protein, DPP8 and DPP9 in primary cell cultures derived from high-grade gliomas, and show that the DPP-IV-like enzymatic activity is negatively associated with their in vitro growth. More importantly, the DPP-IV positive subpopulation isolated from the primary cell cultures using immunomagnetic separation exhibited slower proliferation. Forced expression of the wild as well as the enzymatically inactive mutant DPP-IV in glioma cell lines resulted in their reduced growth, migration and adhesion in vitro, as well as suppressed glioma growth in an orthotopic xenotransplantation mouse model. Microarray analysis of glioma cells with forced DPP-IV expression revealed differential expression of several candidate genes not linked to the tumor suppressive effects of DPP-IV in previous studies. Gene set enrichment analysis of the differentially expressed genes showed overrepresentation of gene ontology terms associated with cell proliferation, cell adhesion and migration. In conclusion, our data show that DPP-IV may interfere with several aspects of the malignant phenotype of glioma cells in great part independent of its enzymatic activity.
Keywords: Primary Cell Culture; signální transdukce; Signal Transduction; regulace genové exprese u nádorů; Humans; Tumor Cells, Cultured; Cell Cycle; dipeptidylpeptidasy a tripeptidylpeptidasy; Dipeptidyl Peptidase 4; mutace; imunomagnetická separace; Dipeptidyl-Peptidases and Tripeptidyl-Peptidases; Cell Adhesion; lidé; zvířata; proliferace buněk; myši; Mice; nádorové buňky kultivované; primární buněčná kultura; transfekce; xenogenní modely - testy protinádorové aktivity; dipeptidylpeptidasa 4; pohyb buněk; Male; Cell Proliferation; stanovení celkové genové exprese; gliom; Cell Movement; Dipeptidases; Transfection; Xenograft Model Antitumor Assays; Animals; buněčná adheze; dipeptidasy; Gene Expression Profiling; Mutation; mužské pohlaví; Gene Expression Regulation, Neoplastic; buněčný cyklus; Glioma; Immunomagnetic Separation